Disturbed intracortical excitability in early Parkinson's disease is l-DOPA dose related: a prospective 12-month paired TMS study - Bares, Martin; Kanovský, Petr; Rektor, Ivan (Parkinsonism & related disorders, 2007)
We were interested to know if chronic l-DOPA treatment in Parkinson's disease (PD) patients could restore impairment of the intracortical excitability, when this difference could occur, and if it was related to the total daily dose of l-DOPA. Twelve patients with early PD were studied using paired transcranial magnetic stimulation before the administration of l-DOPA, and then after 3, 6, and 12 months of l-DOPA treatment. The level of disturbed intracortical excitability strongly correlated with the total daily dose of l-DOPA. The level of cortical excitability in PD patients seems to be indirectly related to the nigro-striatal functioning.
Keywords: následné studie; levodopa; lidé; Middle Aged; Adult; Parkinson Disease; Parkinsonova nemoc; Levodopa; prospektivní studie; funkční lateralita; Female; analýza rozptylu; mozková kůra; vztah mezi dávkou a účinkem léčiva; elektrická stimulace; Analysis of Variance; Humans; Follow-Up Studies; Dose-Response Relationship, Drug; Electric Stimulation; antiparkinsonika; Prospective Studies; lidé středního věku; mužské pohlaví; Cerebral Cortex; Time Factors; ženské pohlaví; Functional Laterality; transkraniální magnetická stimulace; časové faktory; Male; Aged; Transcranial Magnetic Stimulation; dospělí; Antiparkinson Agents; senioři